Operationalising artificial intelligence bills of materials for verifiable AI provenance and lifecycle assurance - Radanliev, Petar; Santos, Omar; Maple, Carsten; Atefi, Kayvan (Frontiers in Computer Science, 2026)
IntroductionArtificial intelligence (AI) systems increasingly rely on complex, multi-layered software supply chains, creating substantial challenges for reproducibility, transparency, and security assurance. Existing software bills of materials inadequately capture AI-specific artefacts such as model lineage, training provenance, and disclosure metadata, limiting verifiable lifecycle governance.MethodsThis study proposes an Artificial Intelligence Bill of Materials (AIBOM) schema that extends the CycloneDX standard through structured schema engineering. The framework integrates cryptographic validation and agent-driven automation to enable machine-verifiable provenance. An autonomous AI pipeline was implemented to conduct continuous environment inspection, vulnerability enrichment, and reproducibility auditing across containerised analytic workflows.ResultsEmpirical evaluation demonstrates 98.7% reproducibility fidelity across replicated executions, 96.2% precision in vulnerability matching against reference datasets, and a 63% reduction in manual oversight compared with conventional documentation-based approaches.DiscussionThe results demonstrate the feasibility of automated provenance assurance and reproducible AI lifecycle validation at scale. The proposed AIBOM framework strengthens software supply chain transparency, enhances provenance integrity, and provides a generalisable methodology for securing AI systems. It further supports alignment with international information security and compliance standards, advancing the scientific foundations of reproducibility engineering in AI-enabled systems.